Kajian Temporal dan Spasial Sebagai Deiksis Konvensional dalam Novel Tokyo dan Perayaan Kesedihan Karya Ruth Priscilia Agelina - Ratri, Risalah Damar; Rumilah, Siti (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze temporal deixis and spatial deixis in the novel Tokyo dan Perayaan Kesedihan by Ruth Priscilia Angelina and find out how the temporal and spatial deixis presented by the author in the novel Tokyo dan Perayaan Kesedihan can create indirect communication between the author and the reader. The research design applies descriptive qualitative data as sources of speech texts in the novels Tokyo dan Perayaan Kesedihan by Ruth Priscilia Angelina. Data collection utilizes documentation techniques and data analysis, classifying data according to the problem formulation and drawing conclusions after the analysis process using Yule's theory regarding temporal deixis and partial deixis. The results of the research are first: 8 temporal deixes, namely in words, and 8 spatial deixes, including the words now, tomorrow, a year, here, then, earlier, and spatial deixis, totaling 8 words, namely here, in the middle, this way, next to, around here, in the forest, and in the city. The two attempts to present temporal deixis and spatial deixis in the novels Tokyo and Celebration of Sadness by the author are given references according to the context of the speech between the characters so that the reader is able to understand the intent and meaning of the temporal deixis and spatial deixis in the speech events between the characters.